Pengaruh Sanksi Perpajakan, Penerapan Self-Assessment System dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Ramdania, Alfiani; Yoshida, Debbie (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research was conducted with the aim of analyzing, knowing and confirming the influence of tax sanctions, implementation of the self-assessment system and taxpayer awareness of SMEs taxpayer compliance (Study of Individual SMEs Taxpayers at KPP Pratama West Tangerang). This research uses primary data obtained from questionnaires distributed to individual SMEs taxpayers at KPP Pratama West Tangerang. The respondents in this research were 100 individual SMEs taxpayers registered at KPP Pratama West Tangerang. The scale used in this research uses a Likert scale. The research design used in this research is causal research. This research uses quantitative methods. The sampling technique used is convenience sampling.  The data analysis method used in the research is descriptive statistics and processed using SmartPLS 4 software. The data analysis technique uses measurement testing (Outer Model) and structural testing (Inner Model). The research results show that tax sanctions have no effect on taxpayer compliance, while the implementation of a self-assessment system and taxpayer awareness have a positive effect on taxpayer compliance.